Administration of Alexandrovskaya Central Penal Colony (1873-1917) - A. A. Ivanov; S. L. Kuras; T. L. Kuras (Научный диалог)
This article explores the formation and activities of the administration of the Alexandrovskaya Central Penal Colony, which played a significant role within the Main Prison Administration of the Russian Empire. The management structure of the Alexandrovskaya Central Penal Colony is examined, along with the staffing schedule of employees. The article also delves into the personnel policy from the establishment of the prison in 1873 until the radical restructuring of the penitentiary system in Russia after the 1917 revolution. Instructional letters outlining the authorities of prison staff are analyzed, as well as the working hours and conditions specific to inmate management at Alexandrovskaya prison. The article scrutinizes the amount of monetary compensation for prison officials and compares it to income levels in other regional prisons. The staffing levels of managerial employees in the prison castle are investigated. Despite low incomes, disorganization in their personal lives, and high levels of daily work stress, there was virtually no turnover among staff. Through examples of individual wardens, it is revealed that they showed a committed attitude towards their duties, striving to make the prison an exemplary institution. The article establishes the fact of career advancement for employees of the Alexandrovskaya Central Penal Colony within the penitentiary system of Irkutsk Province.